Effects of Oral Care Programme on Oral Health Status and Ventilator-Associated Pneumonia Incidence - Seeharach, Orada; Saensom, Donwiwat; Sattayawong, Khampol; Panitchote, Anupol (Journal of Thailand Nursing and Midwifery Council, 2022)
Objective: To investigate ways in which an oral care programme could impact oral health status and incidence of ventilator-associated pneumonia (VAP) in intubated critically ill patients Design: Two-group quasi-experimental research with a pre-test and a post-test Methodology: The subjects were 50 critically ill patients aged 18 years and older, equally divided into a control group and an experimental group. Forty-nine registered nurses were recruited as programme implementers. The research instruments consisted of: 1) the oral care programme; 2) a ventilator-associated pneumonia (VAP) prevention kit; 3) a VAP diagnostic form and an assessment form for oral health status (OHAT); 4) the Silness-Löe Plaque Index (PI); 5) the supra-endotrachial tube cuff secretion score; and 6) a scale measuring nurses’ programme competence, programme adherence, and programme satisfaction. Descriptive statistics, mid p-value, 95% confidence intervals, two-way repeated measures ANOVA, and one-sample T-test were used to analyse the data. Results: After participating in the programme, the experimental group’s mean scores on OHAT, PI, and secretion were lower than those of the control group (OHATexp = 3.9, OHATcon = 5.84; p < 0.001; = 0.46; PIexp = 0.99, PIcon = 1.96; p < 0.001; = 0.54; secretion scoreexp = 1.88 secretion scorecon = 2.63; p < 0.001; = 0.53, respectively). The experimental group’s mean OHAT, PI, and secretions scores on the 2nd, 4th, and 7th day after intubation had a tendency to decrease, whereas the control group’s scores tended to increase. Early-onset VAP was detected in neither group, whilst late-onset VAP was found only in the control group at the rate of 35.08 episodes/1,000 ventilator-days. The VAP incidence difference between the two groups was at -35.08 episodes/1,000 ventilator-days (p = 0.017; 95% CI [-63.16,-7.01]). The participating registered nurses displayed 98.64% (p < 0.001) programme competence, 99.14% (p < 0.001) programme adherence, and 93.8% (p = 0.002) programme satisfaction. Recommendations: The oral care programme helped improve patients’ oral health status, decrease supra-cuff secretion, and reduce VAP incidence. The programme is feasible for clinical application